Hand Compartment Syndrome After Prolonged Robotic-Assisted Laparoscopic Rectal Resection: A Case Report and Literature Review - Han Y. Zhang; Susan Samudre; Xiuli Zhang; Justin J. Lui; Fenghua Li (Case Reports in Anesthesiology)
Hand compartment syndrome is a rare condition due to trauma and vascular obstruction or injury, such as fluid extravasation, vascular obstruction, or arterial injury from arterial line insertion during anesthesia. However, perioperative hand compartment syndrome with no apparent preexisting cause during anesthesia that requires fasciotomy is extremely rare. We report a case on a 54-year-old male with history significant for stage IIIA moderately differentiated adenocarcinoma of the rectum who was scheduled for ultralow rectal resection and cystourethroscopy with insertion of urethral stent. Following surgery, in which he was in a safe-T-Secure positioner in a prolonged Trendelenburg position, the patient developed compartment syndrome of the right hand. This case and literature review highlights the risk for hand compartment syndrome when patients have increased Body Mass Index, positioning involves tucking of the arms, and the procedure duration is prolonged.